Enhancing student writing feedback through teacher–AI collaboration in higher education - Akhter, Shamim; Ajmal, Muhammad; Zeb, Shaista; Saira; Prasad, Rabindra Dev (Journal of Education and e-Learning Research, 2025)
The objective of this research is to explore the collaborative role of AI and teachers in providing feedback on written assignments. Teacher feedback is key to improving students’ writing, but now there is AI that can perform the same role. The study uses a combination of classroom testing and questionnaires to collect information. Forty students studying BS English at Shaikh Ayaz University, Shikarpur, Pakistan participated, receiving feedback on their papers from a teacher, and the same assignments also received AI-generated feedback. The results were analyzed thematically and interpreted accordingly. The students’ perspective is that AI tools helped students improve grades by addressing grammar and sentence-level issues. Teachers benefited from less workload when AI was included; the feedback was faster, encouraging students to revise their work more readily. Human intervention is still required to ensure better quality and more intelligent AI suggestions. The findings suggest that teachers and AI work more effectively together to provide feedback on writing, including grammar and formal expression of opinions. The research implies that adopting AI into the curriculum carries responsibilities that need to be formally stated in policies and tested in classroom settings.